Perceptions derived from experiences on physical education lessons and their consequences in sport habits in non-compulsory secondary education students - E. Torre; D. Cárdenas; E. García (Asociación Española de Ciencias del Deporte, 2010)
This research, which has been made with students of the third course of BUP in Granada, analyses the relation between the perceptions derived from the received experiences in the physical education classes and its effects on the voluntary physical activity, in their spare time. For it, to structure the work starting with an introduction in which the conceptual framework, objectives and hypothesis are established, followed by a description of the method, results together with the discussions and finally the conclusions, has been considered. KEY WORDS: Sports habits, physical education, perceptions, motivations, experiences and attitudes.